Attitude towards smoking and second hand smoke exposure among school going adolescents in India - Neeti Rustagi; Lobzang Norbu; Anil Kumar; Manoj Kumar Verma (Wolters Kluwer Medknow Publications, 2017)
Exposure to second hand smoke (SHS) among school going adolescents is a public health problem. It is important to understand the possible sources and the attitude among adolescents which increases the risk of such exposure. The objective of present study was to assess exposure and attitude of school going adolescents towards second hand smoke. This cross-sectional survey was conducted among students of a school in India which is supported by funding from para- military forces to ensure quality education to children of para-military personnel's. Students from class VII to XII were included and data was collected using Global Youth Tobacco Scale. Exposure to SHS in past one week inside home was found to be 45% and in public places 76.6%. Though smoking from other people was reported to be harmful (89%) and discussion about harmful effects of smoking is carried out by school authorities (73.2%) and families (75.9%) yet attitude towards SHS among adolescents is favorable and is considered helpful in enhancing socialization and making personality attractive. Second hand smoke exposure among school adolescents is high and strategies designed to reduce smoking among them need to specially target positive image associated with smokers.